Prospects of Implementing the Flipped Classroom Blended Learning Model among Lecturers in African Universities - Muhuro, Patricia; Kang'ethe, Simon (Research in Social Sciences and Technology- OpenED Network, 2025)
The flipped classroom is an emergent digital pedagogy credited with virtuous and student-centric characteristics of increased learning. The purpose of this study was to discuss the implementation of the Flipped Classroom Blended Learning Model among lecturers in African Universities. The study employed a qualitative literature review, after reviewing 15 articles drawn from EBSCO host, Web of Science, Scopus, and Google Scholar. Findings reflected that: The flipped classroom model is virtuously unique, student-centric, facilitative, and interactive, employs active learning, and faces daunting implementation challenges in Afrocentric settings. The paper calls for more training among lecturers in Afrocentric settings to raise lecturers' state of professional development.